2006
DOI: 10.1097/01.inf.0000199314.88063.4c
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Tuberculous Meningitis in Children in Durban, South Africa

Abstract: The changes in the cerebrospinal fluid (CSF) in early TBM can be nonspecific and can change rapidly; therefore, CSF studies should always include culture and susceptibility testing. Factors that contributed to the high mortality were disseminated TB, HIV infection, delay in diagnosis and treatment, the absence of a standardized approach to the management of MDR-TBM and the poor CSF penetration of most MDR-TB drugs. MDR-TB therapy should be considered if there is a history of TB: a MDR-TB contact or a poor clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 8 publications
(4 reference statements)
0
34
0
Order By: Relevance
“…In some of the published series, the Medical Research Council grading system was not predictive in MDR TBM cases (145,148). Although the mortality among these MDR TBM cases is quite high, many of the patients never actually received adequate therapy prior to their demise (145,148). MDR tuberculosis therapy should be considered if there is a history of prior tuberculosis treatment, contact with a patient with MDR tuberculosis, or a poor clinical response to first-line TB therapy within 2 weeks despite a firm diagnosis and an adequate adherence to treatment.…”
Section: Antibiotic Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…In some of the published series, the Medical Research Council grading system was not predictive in MDR TBM cases (145,148). Although the mortality among these MDR TBM cases is quite high, many of the patients never actually received adequate therapy prior to their demise (145,148). MDR tuberculosis therapy should be considered if there is a history of prior tuberculosis treatment, contact with a patient with MDR tuberculosis, or a poor clinical response to first-line TB therapy within 2 weeks despite a firm diagnosis and an adequate adherence to treatment.…”
Section: Antibiotic Therapymentioning
confidence: 99%
“…While the importance of multiply drug-resistant (MDR) tuberculosis (defined by resistance to both isoniazid and rifampin) has been well documented in the literature, the features of MDR tuberculosis in TBM have been characterized mostly by case reports and small case series (17,28,29,44,47,69,145,148,196,199,200,238). With MDR tuberculosis, time to identification of resistance is often prolonged, and therefore, time to appropriate antituberculosis therapy is delayed (up to 10 weeks) or even initiated after the disease has advanced too far (145,148). In some of the published series, the Medical Research Council grading system was not predictive in MDR TBM cases (145,148).…”
Section: Antibiotic Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…7 These delays could lead to progression of disease, increased risk of infectiousness of children, greater risk of disease complications such as tuberculous meningitis, and higher rates of morbidity and mortality. 8,9 Paediatric drug-resistant tuberculosis is a neglected concern, with few children being treated relative to the estimated disease burden. 10 WHO guidelines for the treatment of drug-resistant tuberculosis in adults are based on evidence from meta-analyses of individual patients' data.…”
Section: Introductionmentioning
confidence: 99%
“…Our case also differs from the case presented by Das et al 2012, in the absence of the dissemination to any other organ and also the present case is a pediatric case (5). Besides, a study carried in the South Africa showed the presence of MDR-TB in pediatric age groups, but this study mainly involved the HIV positive cases of TB meningitis and in almost all these cases the diagnosis was made posthumously (13). Our case differs from this South African study due to the involvement of the different extrapulmonary site, i.e., pleura, with early diagnosis based on the high degree of suspicion and the HIV negative status of the case (13).…”
Section: Discussionmentioning
confidence: 99%